2015
DOI: 10.1007/s00382-015-2495-3
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Impact of domain size on the simulation of Indian summer monsoon in RegCM4 using mixed convection scheme and driven by HadGEM2

Abstract: The original version of the article has been published with a sub title 'Impact of domain size on ISM simulations' printed just below the main title. It should be removed from the title page of the article. Further, the running head in the right hand pages should read as 'Impact of domain size on ISM simulations' instead of 'mixed convection scheme and driven by HadGEM2'.The online version of the original article can be found under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The CORDEX datasets showed promising improvement in simulating several climatic features for many countries (Endris et al, 2013), but for India, no significant improvements are exhibited, although efforts have been made by several authors (Mishra et al, 2018b;Jain et al, 2019a). Previous regional climate modeling studies showed useful results at the levels of homogenous zones and cities (Dash et al, 2013(Dash et al, , 2015. Based on some previous studies, one can infer that some of the dynamically downscaled climate products are useful, even at the city level (Dash et al, 2013(Dash et al, , 2015Pattnayak et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The CORDEX datasets showed promising improvement in simulating several climatic features for many countries (Endris et al, 2013), but for India, no significant improvements are exhibited, although efforts have been made by several authors (Mishra et al, 2018b;Jain et al, 2019a). Previous regional climate modeling studies showed useful results at the levels of homogenous zones and cities (Dash et al, 2013(Dash et al, , 2015. Based on some previous studies, one can infer that some of the dynamically downscaled climate products are useful, even at the city level (Dash et al, 2013(Dash et al, , 2015Pattnayak et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Previous regional climate modeling studies showed useful results at the levels of homogenous zones and cities (Dash et al, 2013(Dash et al, , 2015. Based on some previous studies, one can infer that some of the dynamically downscaled climate products are useful, even at the city level (Dash et al, 2013(Dash et al, , 2015Pattnayak et al, 2013). However, there are questions about the robustness of those results.…”
Section: Introductionmentioning
confidence: 99%